PENERAPAN MEDIA PEMBELAJARAN ANIMATED DRAWINGS UPAYA DALAM MENINGKATKAN HASIL BELAJAR MENGGAMBAR SISWA DI SDIT AL-QONITA - Ratna Rahayu Pertiwi; Setria Utama Rizal; Muhammad Syabrina (Jurnal Bilqolam Pendidikan Islam, 2025)
This study aims to determine the application of Animated Drawings learning media in improving learning outcomes in drawing, as well as to determine student learning outcomes after the application of Animated Drawings learning media. The method used is Classroom Action Research (CAR), which consists of stages of planning, action, observation, and reflection. The subjects in this study consisted of 22 fourth grade students at SDIT AL-Qonita Palangka Raya, where 11 female students and 11 male students. With data collection techniques consisting of observation, documentation, and tests. The results of this study indicate that in the application of Animated Drawings learning media, it can create learning that is increasing, creative, effective in the quality of learning outcomes and is able to encourage students to think critically. In addition, the activities of teachers and students during the learning process can also have an effect, but both increase with very good criteria. The students' learning outcomes from cycle I were on average 7.409 and classical completeness was 23%, and increased in cycle II with an average value of 12.409 and classical completeness of 77%.